The effect of ownership structure on dividend policy of manufacturing companies - Cynthia Valentina; Liliana Inggrit Wijaya; Endang Ernawati (Manajemen dan Bisnis, 2022)
This study aims the impact of ownership structure on dividend on manufacturing companies listed on the Indonesia Stock Exchange and Malaysia Stock Exchange for the period 2015-2019. This study uses regression method as quantitative measurement level. The research used objects as many as 455 observations on the Indonesia Stock Exchange and 500 observations on the Malaysia Stock Exchange. The independent variables used in this research are foreign ownership, family ownership, and institutional ownership. The results of the study using observations on the Indonesia Stock Exchange found that family ownership and institutional ownership have a significant positive effect, while foreign ownership has an insignificant negative effect on dividend payout ratio. The results of the study using observations on the Malaysia Stock Exchange found that institutional ownership has a significant positive effect, while the rest has an insignificant positive on dividend payout ratio.